Keanekaragaman dan pola keberadaan lalat buah (Diptera: Tephritidae) di Provinsi Sumatera Selatan - Yulia Pujiastuti; Chandra Irsan; Siti Herlinda; Laila Kartini; Eka Yulistin (Jurnal Entomologi Indonesia, 2020)
Fruit flies attack mostly on fruit vegetables and fresh consumed fruit. Symptoms of damage is decaying of fruit surface resulting to fruit falling. Data on the diversity of fruit fly species in South Sumatra and their patterns of presence have not been widely reported. The aim of the research was to study diversity and presence patterns of fruit flies based on the host and trap. The research was conducted using a survey method in 9 cities and districts in South Sumatra Province. Fruit flies were collected by collecting infected fruit and using traps containing cue lure (CL) and methyl eugenol (ME). There were 24 types of plants observed, including fruit, vegetables, and fruit for consumption. Fruit flies identification was carried out by observing external morphological characteristics. The identification resulted 18 species in which CL and ME trap 10 and 7 species, respectively. One species (Bactrocera latrifons) did not trapped in both traps. Among 18 species, 7 of them were obtained from fruit collections. The type of attractant affected species diversity and number of fruit flies caught. B. latifrons was only found in fruit rearing. The altitude of observation area affected fruit flies diversity. All species were found in the lowlands, except B. ascitus, B. cilifera, and B. latrifons. In the moderate lands and highlands, the number of fruit fly species found was less than in the lowlands.